2022
DOI: 10.3390/land11030329
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Soil Physical Properties Related to a High Mechanization Level in the Row Thinning of a Korean Pine Stand

Abstract: In ground-based harvesting, machine traffic can cause soil physical disturbances including excessive compaction, the displacement of the soil surface and topsoil, and rutting. These impacts can indirectly hamper seedling survival and tree growth because of reduced soil permeability and root growth. However, the extent of soil disturbance in mechanized row thinning by harvester and forwarder systems in South Korea is unclear. Therefore, our objectives were to determine the impacts of two types of harvesters, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In recent years, the mechanized row-thinning application, which uses a harvester and forwarder, has resulted in increased productivity and work safety [20]. For example, Hwang et al [6] reported that although mechanized thinning is an effective tool to control overstocked stands and restore ecosystems, it can possibly expose the remaining damage to the stand.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the mechanized row-thinning application, which uses a harvester and forwarder, has resulted in increased productivity and work safety [20]. For example, Hwang et al [6] reported that although mechanized thinning is an effective tool to control overstocked stands and restore ecosystems, it can possibly expose the remaining damage to the stand.…”
Section: Introductionmentioning
confidence: 99%
“…Timber is felled and extracted using various technologies with different levels of mechanization, including fully mechanized, semi-mechanized, and motor-manual methods [1,2]. Even though mechanized harvesting technologies can provide clear benefits by improving productivity and safety, ground-based machine traffic can inherently impact forest ecosystems, particularly forest soils [3][4][5] in the form of compaction, rutting, and displacement [6,7]. The severity and extent of soil disturbance during mechanized operations depend on several factors such as the harvesting system, silvicultural treatments, terrain slope, soil type, and texture [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mechanized operations involving harvesters and forwarders on both gentle and steep terrains have led to increased productivity but fewer job opportunities for loggers in South Korea (hereafter, Korea; [16]). A harvester-forwarder system can replace manual tree felling, processing, and shovel and cable extraction; however, mechanized operations are more likely to cause severe soil disturbances [3,7,17]. Several investigations on soil disturbance related to cut-to-length systems in Korea have examined conventional chainsaw felling and small-shovel extraction, as well as mechanized harvesting systems, such as harvester-forwarder operations [7,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation